A new endoscopic minimal invasive approach for pudendal nerve and inferior cluneal nerve neurolysis: An anatomical study. Issue 3 (26th October 2017) - Ploteau, Stéphane; Robert, Roger; Bruyninx, Luc; Rigaud, Jérome; Jottard, Katleen
Abstract : Aim: To describe a new minimal invasive approach of the gluteal region which will permit to perform neurolysis of the pudendal and cluneal nerves in case of perineal neuralgia due to an entrapment of these nerve trunks. Method: Ten transgluteal approaches were performed on five cadavers. Relevant anatomic structures were dissected and further described. Neurolysis of the pudendal nerve or cluneal nerves were performed. Landmarks for secure intraoperative navigation were indicated. Results: The first operative trocar for the camera was inserted with regards to the iliac crest in the deep gluteal space. With the aid of pneumodissection, the infragluteal plane was dissected. The piriformis muscle was identified as well as the sciatic and the posterior femoral cutaneous nerve. Consequently, the sciatic tuberosity was visualized together with the cluneal nerves. Hereafter, the second trocar was introduced caudal to the first one and placed on an horizontal line passing at the level of the coccyx, allowing access to the ischial spine and the visualization of the pudendal nerve and vessels. A third 5 mm trocar was then inserted medial from the first one, permitting to dissect and transsect the sacrospinous ligament. The pudendal nerve was subsequently transposed and followed on its course in the pudendal channel. Conclusions: A reliable exploration of the gluteal region including identification of the sciatic, pudendal, and posterior femoral cutaneous nerves is feasible using a minimal invasive transgluteal procedure. Consequently, the transposition of the pudendal nerve and the liberation of the cluneal nerves can be performed.